2017
DOI: 10.1149/2.0571712jes
|View full text |Cite
|
Sign up to set email alerts
|

Linking Foreign Cationic Contamination of PEM Fuel Cells to the Local Water Distribution

Abstract: Cationic contamination of polymer electrolyte fuel cells is known to cause performance degradation, particularly due to displacement of protons by foreign cations in the ionomer. Recent findings however, show that mass transport is a critical mechanism in the contamination process. X-ray computed tomography is used to examine the salt precipitation within the cathode diffusion media following in situ cation contamination experiments. Statistical analysis of the tomographic data is performed to examine the salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Salt precipitation is possible and preferentially occurs in flow channels and the gas diffusion layer under landings, occluding transport paths and modifying component hydrophobicity and water management. One or more of these effects were invoked to explain increases in mass transfer losses observed during Co 2+ (from PtCo alloy catalyst dissolution), , NH 4 + (reformate impurity), Ca 2+ (a component of roadside desalting agents, seawater component), K + (seawater component), Ba 2+ , Al 3+ , and Cl – (seawater component) contamination. Organic species adsorb on PEMFC C (gas diffusion layer, sublayer, catalyst support) and Pt materials, which, respectively, alter surface hydrophobicity and liquid water management, and increase the real current density by partially covering catalyst sites.…”
Section: Introductionmentioning
confidence: 99%
“…Salt precipitation is possible and preferentially occurs in flow channels and the gas diffusion layer under landings, occluding transport paths and modifying component hydrophobicity and water management. One or more of these effects were invoked to explain increases in mass transfer losses observed during Co 2+ (from PtCo alloy catalyst dissolution), , NH 4 + (reformate impurity), Ca 2+ (a component of roadside desalting agents, seawater component), K + (seawater component), Ba 2+ , Al 3+ , and Cl – (seawater component) contamination. Organic species adsorb on PEMFC C (gas diffusion layer, sublayer, catalyst support) and Pt materials, which, respectively, alter surface hydrophobicity and liquid water management, and increase the real current density by partially covering catalyst sites.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a liquid water pathway from the flow field to MEA is suspected of transporting the metal ions from the bipolar plate into the gas diffusion layer (GDL). 16 In-situ visualization of water transport in MEAs have shown that water accumulates in the GDL substrate under the land of the bipolar plates, where it is cooler than the channel region as heat is removed through the lands. 17,18 A microporous layer (MPL), consisting of carbon and polytetrafluoroethylene (PTFE), is coated onto the GDL substrate fibers to provide good interfacial contact with the catalyst layer (CL) and enhance water removal from the CL.…”
mentioning
confidence: 99%
“…Prior work on understating the cation contaminant transport was conducted through the ex situ introduction of the cation into the membrane or MEA by ion-exchanging the cation with protons via soaking the membrane or MEA in a contaminant salt solution 23 or in situ by introducing a cation salt solution along with fuel or the oxidant stream of the fuel cell. 16,[24][25][26] The ex situ studies provide an understanding of the effects of the cation on the performance of the fuel cell. Studies of injecting contaminant have shown that the GDL plays a crucial role, and the hydrophobic MPL acts as a protective barrier due to the higher capillary pressure of the hydrophobic pores not allowing liquid water transport, preventing the cation from transporting to the membrane at the beginning of life (BOL).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The contaminants from airborne impurities (SO 2 , H 2 S, CO, NO x , and bromomethane), [3][4][5][6][7][8][9][10][11][12][13] fuel impurities in hydrogen(NH 3 , CO, hydrocarbons, glycols, and alcohols), [14][15][16][17][18][19][20][21] inorganic metal cations(sodium, calcium, potassium, iron, nickel, and silicon etc.) [22][23][24][25][26][27][28][29][30][31][32][33] from gasket, bipolar plates, catalyst alloys, and deicer etc., and also from organic leachates(aniline, toluene, alcohols, glycols, propylene, methyl methacrylate) [34][35][36][37][38][39][40][41][42][43] derived from fuel cell systems including stack, structural plastic materials, and assembly aids.…”
mentioning
confidence: 99%